Self-rated health, interviewer-rated health, and objective health, their changes and trajectories over time, and the risk of mortality in Chinese adults - Shan, Shiyi; Cao, Jin; Tang, Ke; Cheng, Siqing; Ren, Ziyang; Li, Shuting; Sun, Weidi; Hou, Leying; Yi, Qian; Chen, Dingwan; Song, Peige (Frontiers in Public Health, 2023)
Background Self-rated health (SRH), interviewer-rated health (IRH), and objective health reflect the overall health status from different aspects. This study aimed to investigate the associations of SRH, IRH, and objective health with mortality among Chinese elderly. Methods This study used data from the 2008 (baseline), 2011, 2014 and 2018 waves of the Chinese Longitudinal Healthy Longevity Survey. SRH and IRH were evaluated by questionnaire. Objective health was evaluated by the Chinese multimorbidity-weighted index (CMWI), which incorporated 14 diagnosed chronic diseases. SRH, IRH, and CMWI were assessed as: 1) baseline levels; 2) longitudinal changes by subtracting the values obtained in 2008 from the corresponding values in 2014; 3) trajectories by Group-Based Trajectory Modelling respectively. The Cox proportional hazards model was used to explore the associations of baseline SRH, IRH, and CMWI, their changes, and trajectories with mortality. Results A total of 13,800 participants were included at baseline (2008). The baseline SRH ([hazard ratio] 0.93, [95% confidence interval] 0.91-0.96), IRH (0.84, 0.81-0.87), and CMWI (0.99, 0.98-1.00) in 2008 were significantly associated with 10-year mortality (2008 to 2018). Among 3,610 participants, the changes of SRH (0.93, 0.87-0.98), IRH (0.77, 0.71-0.83), and CMWI (0.97, 0.95-0.99) from 2008 to 2014 were significantly associated with 4-year mortality (2014 to 2018). The trajectories were divided into "high SRH/IRH/CMWI" and "low and declining SRH/IRH/CMWI". Compared with "low and declining SRH/IRH/CMWI", “high SRH” (0.58,0.48-0.70), “high IRH” (0.66, 0.55-0.80), and “high CMWI” (0.74, 0.61-0.89) from 2008 to 2014 were significantly associated with 4-year mortality (2014 to 2018). Conclusion Baseline SRH, IRH, and CMWI, their changes and trajectories are all associated with mortality in Chinese elderly. It is necessary to promote the use of cost-effective indicators in primary medical institutions to improve the health management of the elderly.